Concomitant benzodiazepine and opioids decrease sleep apnoea risk in chronic pain patients. Issue 3 (25th August 2020) - Mir, Soodaba; Wong, Jean; Ryan, Clodagh M.; Bellingham, Geoff; Singh, Mandeep; Waseem, Rida; Eckert, Danny J.; Chung, Frances
Background: The concurrent use of sedating centrally acting drugs and opioids by chronic pain patients occurs routinely despite concerns of negative impacts on respiration during sleep. The effects of centrally acting drugs and opioids on sleep apnoea have not been well characterised. The objective of this study was to assess the effect of concomitant centrally acting drugs and opioids on the prevalence and severity of sleep apnoea in chronic pain patients. Methods: We conducted a prospective cohort study at five chronic pain clinics. Each participant underwent an in-laboratory polysomnography and daily morphine milligram equivalents were calculated. Participants were grouped into centrally acting drugs and opioid users versus sole opioid users. Results: Of the 332 consented participants, 204 underwent polysomnography and 120 (58.8%) had sleep apnoea (72% obstructive, 20% central, and 8% indeterminate sleep apnoea). Overall, 35% (71 of 204) were taking opioids alone, and 65% (133 of 204) were taking centrally acting drugs and opioids. There was a 69% decrease in the odds of having sleep apnoea (apnoea–hypopnoea index ≥5 events·h −1 ) in participants taking benzodiazepine/opioids versus sole opioid users (OR 0.31, 95% CI:0.12–0.80, p=0.015). Additionally, concomitant benzodiazepine/opioids versus sole opioid use was associated with a decrease in respiratory arousal index scores (p=0.03). Mean overnight S pO2 was approximately 1% lower in the concomitant benzodiazepine/opioids group versus sole opioid users (93.1±2.5 versus 94.4±2.1%, p=0.01). Conclusion: In chronic pain patients on opioids, administration of certain benzodiazepine sedatives induced a mild respiratory depression but paradoxically reduced sleep apnoea risk and severity by increasing the respiratory arousal threshold. There may be potential to reduce sleep apnoea risk and severity in specific chronic pain patients on opioids using certain benzodiazepine sedatives by selecting those with a low respiratory arousal threshold in whom sleep promotion may stabilise breathing https://bit.ly/2Zj4WX1